Improving access to oral pre-exposure prophylaxis for HIV among international migrant populations - Warittha Tieosapjaroen, PharmD; Ying Zhang, MPH; Christopher K Fairley, ProfPhD; Lei Zhang, PhD; Eric P F Chow, PhD; Tiffany R Phillips, PhD; Heather-Marie Schmidt, PhD; Benjamin R Bavinton, PhD; Darryl O'Donnell, PhD; Limin Mao, PhD; Andrew Grulich, ProfPhD; Jason J Ong, PhD (Elsevier, 2023)
Summary: Pre-exposure prophylaxis (PrEP) is recommended for people susceptible to HIV acquisition, and the scale-up of PrEP programmes has contributed to new HIV case reductions at a population level. However, international migrants continue to be disproportionately affected by HIV. Understanding barriers and facilitators to PrEP implementation among international migrants can optimise PrEP use among this population and ultimately reduce HIV incidence worldwide. We reviewed the evidence regarding factors influencing PrEP implementation among international migrants; 19 studies were included. The barriers and facilitators at the individual level were related to knowledge and risk perception of HIV. Cost, provider discriminations, and health system navigation influenced PrEP use at the service level. Positive or negative perception towards LGBT+ identities, HIV, and PrEP users affected PrEP use at the societal level. Most existing PrEP campaigns do not target international migrants; therefore, culturally tailored approaches for people from different backgrounds are warranted. Potentially migration-related and HIV-related discriminatory policies must be reviewed to increase access to HIV prevention services to end HIV transmission at a population level.